STOCK VALUATION ANALYSIS USING DIVIDEND DISCOUNTED MODEL DAN FREE CASH FLOW TO EQUITY OF TECHNOLOGY COMPANIES LISTED AT IDX - Christian Sihotang; Francis Hutabarat (Klabat Journal of Management, 2023)
The economic situation in Indonesia has suffered a major hit in various sectors since the end of 2019. This study aims to analyze the Valuation of Technology Company Shares listed on the Indonesia Stock Exchange using the Dividend Discount Model and Free Cash Flow to Equity. This study uses a sample of 8 companies from 35 technology companies on the Indonesia Stock Exchange. The research data compares stock valuations in 2019, 2020 and 2021 before, during and after Covid 19. Statistical analysis uses the Kolmogorov-Smirnov one sample, Pair-Sample t-test, and descriptive statistical analysis. The research results show that there is a significant difference between the valuation of free cash flow to equity shares in 2019 before Covid 19 and in 2020 during Covid 19 in technology companies on the Indonesia Stock Exchange. Conversely, for a comparison of 2019 and 2021 stock valuations, no significant difference was found and for the dividend discount model it was found that there was no significant difference between stock valuations in 2019 and in 2020, and 2021. Keywords: Dividend discount model, free cash flow to equity, stock valuation Situasi ekonomi di Indonesia mengalami pukulan besar di berbagai sektor sejak akhir era 2019. Penelitian ini hendak menganalisis Valuasi Saham perusahaan Teknologi yang terdaftar di Indonesian Stock Exchange dengan menggunakan Dividen Discounted Model dan Free Cash Flow to Equity. Penelitian ini menggunakan sample 8 perusahaan dari 35 perusahaan teknologi di Indonesian Stock Exchange. Data penelitian membandingkan valuasi saham pada tahun 2019, 2020 dan 2021 pada masa sebelum, saat, dan sesudah covid-19. Analisa statistik menggunakan one sample Kolmogorov-Smirnov, Pair-Sample t-test, dan analisa statistik deskriptif. Hasil penelitian menunjukkan bahwa ada perbedaan yang signifikan antara valuasi saham free cash flow to equity pada tahun 2019 sebelum covid-19 dan pada tahun 2020 saat covid-19 di perusahaan teknologi di Indonesia Stock Exchange. Sebaliknya, untuk perbandingan valuasi saham 2019 dan 2021, ditemukan tidak ada perbedaan yang signifikan dan untuk dividend discounted model ditemukan tidak ada perbedaan signifikan antara valuasi saham pada tahun 2019 dan pada tahun 2020, dan 2021. Kata Kunci: dividend discount model, free cash flow to equity, valuasi saham